Модифікація астаксантином радіаційно-індукованої хромосомної нестабільності в соматичних клітинах людини in vitro - Курінний, Д.А. (Фактори експериментальної еволюції організмів, 2016)
Aim. Investigation the influence of astaxanthin on the radiation-induced cytogenetic effect in human peripheral blood lymphocytes. Methods. Astaxanthin in optimal concentration (20.0 μg/ml), established in the previous own research, added to culture of human peripheral blood lymphocytes prior to incubation before gamma irradiation in dose 1 Gy. Cultivation of peripheral blood lymphocytes received from five conditionally healthy volunteers during 48 hours; staining of metaphase chromosome slides; scoring of slides under the microscope (cytogenetic analysis); identification of the full range of chromatid and chromosome aberration types had been fulfilled. Results. Established that meangroup frequency of chromosome aberrations which were presented only by acentrics was 2.57 ± 0.35 per 100 metaphases in intact cultures and 2.36 ± 0.38 per 100 metaphases under astaxanthin exposure. After irradiation the total frequency of chromosome aberrations increased to 24.47 ± 1.73 per 100 metaphases due to raising the level of simple acentrics (7.29 ± 1.05 per 100 metaphases) and induction the exchanges – dicentrics, centric rings and abnormal monocentrics (12.80 ± 1.35; 2.75 ± 0.66; 0.49 ± 0.28 per 100 metaphases, respectively). The treatment of irradiated human peripheral blood lymphocytes by astaxanthin led to significant decrease the frequency of chromosome aberrations (8.40 ± 0.90 per 100 metaphases) due to decline of unstable cytogenetic markers of radiation exposure – dicentrics and centric rings (1.90 ± 0.44 and 0.42 ± 0.21 per 100 metaphases, respectively) and reduction the total frequency of double fragments and acentric rings (5.28 ± 0.82 per 100 metaphases). Conclusions. Data obtained testify about powerful genoprotective and radioprotective potential of astaxanthin in studied concentration. Keywords: astaxanthin, frequency of chromosome aberrations, human peripheral blood lymphocytes, gamma irradiation.